Valorization of coal mine effluents — Challenges and economic opportunities - Nikhil Dilip Pawar; Steve Harris; Krzysztof Mitko; Gijsbert Korevaar (Water Resources and Industry, 2022)
Coal-mine effluent treatment has the potential to both reduce the environmental impact of the effluent and provide economic opportunities by recovering valuable minerals and clean water. In this study, we modeled a novel treatment process, which includes nanofiltration (NF), two-step crystallization, reverse osmosis (RO), electrodialysis (ED), multi-effect distillation (MED), and a NaCl crystallizer, and performed a techno-economic analysis of its full-scale implementation, using a circular economy approach. We estimated the thermal and electrical energy consumption to be 745.5 kWhth/tonNaCl and 565.1 kWhel/tonNaCl (or 13.6 kWhth and 10.3 kWhel per m3 of feed effluent), respectively. The levelized cost of the NaCl salt that accounts for the revenue from the plant's co-products (Mg(OH)2, CaSO4 and, pure water) was estimated to be 203 USD/tonNaCl. The economic viability of the treatment chain can be improved by using renewable electricity sources, reducing the total expenditure on NF and RO, and integrating alternate technologies into the treatment plant.